PERTUMBUHAN DAN PERKEMBANGAN DIPENGARUHI CAHAYA GROWTH AND DEVELOPMENT ARE INFLUENCED BY LIGHT - Laura Renita; Wahyu Satria (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Growth and development occur simultaneously. The difference is that growth can be measured, such as how much something exists or how large it is. However, development relates to quality, such as changes in how something functions. This study aims to determine the importance of light for mung bean growth. Qualitative research was used in this study. The study was conducted over 7 days in the PGSD VI D class, room 206, STKIP Al Maksum Langkat. The results of observations of mung bean sprouts over a week revealed that the amount of light they received significantly impacted their growth.